2020
DOI: 10.1111/zph.12767
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced threat of tick‐borne infections within cities? Assessing public health risks due to ticks in urban green spaces in Helsinki, Finland

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 70 publications
3
24
0
2
Order By: Relevance
“…In the current study, we have con rmed the occurrence of three Babesia species, out two of them (B. microti and B. venatorum), are considered to be pathogenic for humans. Nonetheless, the Babesia prevalence in I. ricinus removed from humans is rather low (1.3%) and similar to other European studies on engorged as well as questing I. ricinus ticks [9,35,65,78].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the current study, we have con rmed the occurrence of three Babesia species, out two of them (B. microti and B. venatorum), are considered to be pathogenic for humans. Nonetheless, the Babesia prevalence in I. ricinus removed from humans is rather low (1.3%) and similar to other European studies on engorged as well as questing I. ricinus ticks [9,35,65,78].…”
Section: Discussionsupporting
confidence: 88%
“…afzelii genospecies/ species occurrence. Similar year-to-year variations were shown in I. ricinus ticks removed from humans in Germany [37,38] and in questing ticks collected in Europe [9,22,60]. It is well-known that the distribution and prevalence of Borrelia spp.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Although these demands could be met by a precise study design, the obtained density index might still significantly deviate from the 'absolute' density of host-seeking ticks because of the low sampling efficiency of any single cloth dragging over a uniquely selected strip of vegetation and because, depending on the ambient humidity, questing ticks must occasionally descend from vegetation into the moister conditions of the litter and soil (Needham and Teel 1991;Hermann and Gern 2015). When sampling ticks and estimating their abundance in an area, repetitions to increase the precision of the density index are often performed on adjacent sampling transects (e.g., Mays et al 2016;Kjaer et al 2019;Sormunen et al 2020b), instead of repeating the dragging on the very same transect, with the latter being the method used here.…”
Section: Introductionmentioning
confidence: 99%
“…Even though ticks are highly adaptable and able to colonize various habitats, they are usually recognized (mainly among the public) as parasites typically found in rural or forest areas. This notion is contradicted by several recent studies which showed that ticks are also frequently observed in urban and peri-urban habitats [5][6][7][8]. Typical urban areas inhabited by ticks include recreational areas, parks and cemeteries [9][10][11].…”
Section: Introductionmentioning
confidence: 91%